Hemp-based all-cellulose composites through ionic liquid promoted controllable dissolution and structural control. (1st May 2020) - Chen, Ke; Xu, Weixin; Ding, Yun; Xue, Ping; Sheng, Pinghou; Qiao, Hui; He, Jimin
Highlights: A novel controllable dissolution method to prepare all cellulose composites was proposed. The partial dissolution mechanism was systematically explained by cooperation of optical and polarizing microscope. Improved mechanical properties of samples were achieved through 'self-welding' effect. This environment-friendly and low cost preparation method provided a promising pathway for large-scale application of ACC. Abstract: All-cellulose composites (ACC) were effectively prepared by a low energy consumption strategy. The ionic liquid of 1-butyl-3-methylimidazolium chloride (BMIMCl) was used to immerse hemp fabric before hot-pressing process at a relative low temperature. The tensile strength and modulus of prepared ACC reached 81.1 MPa and 1.50 GPa, respectively. The dissolution mechanism of ACC by BMIMCl was successfully observed by the cooperation of optical microscope and polarizing microscope. Scanning electron microscope (SEM), X-ray diffraction (XRD), thermal gravimetric analysis (TGA) and mechanical testing were carried out to investigate the effect of hot-pressing temperature on the properties of ACC samples. ACC sample exhibited the highest mechanical performance at hot-pressing temperature of 120 °C. This work provided a simple and promising pathway for industrial application of high performance and environmental-friendly all-cellulose composites.